2021
DOI: 10.26434/chemrxiv-2021-850lc
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Design and synthesis of novel orexin 2 receptor agonists based on naphthalene skeleton

Abstract: A novel series of naphthalene derivatives were designed and synthesized based on the strategy focusing on the restriction of the flexible bond rotation of OX2R selective agonist YNT-185 (1) and their agonist activities against orexin receptors were evaluated. The 1,7-naphthalene derivatives showed superior agonist activity than 2,7-naphthalene derivatives, suggesting that the bent form of 1 would be favorable for the agonist activity. The conformational analysis of 1,7-naphthalene derivatives indicated that th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…C107 2.57 , F227 5.42 , D211 4.84 , H350 7.39 ) but exclusivism of these interactions as the statedeterminants for OX2R agonism is still reluctant. [41][42][43][44][45] Regarding the in silico studies reported by Hong et al, the molecular dynamics simulations of OX2R-OXB in a pure POPC bilayer, taking 1 µs in NPT/OPLS3e ensemble with TIP3P water models and positional restriction force of 5 kcal/mol/Å 2 imposed on selected heavy atoms, confirmed nearly a whole-run stable RMSD for heavy atoms forming the OX2R-OXB interface. 27 In agreement with other in silico studies, Hong et al accepted the hypothesis that GPCRs occur in several elastic metastates on the activation potential coordinate and GPCR agonists rather shift the equilibrium towards populating more the active state than cause a conformational transition to a local energetic minimum, that is in the case of OX2R rotated outswing of TM6, upward movement of TM3, and centripetal shift of TM2.…”
Section: Introductionmentioning
confidence: 80%
“…C107 2.57 , F227 5.42 , D211 4.84 , H350 7.39 ) but exclusivism of these interactions as the statedeterminants for OX2R agonism is still reluctant. [41][42][43][44][45] Regarding the in silico studies reported by Hong et al, the molecular dynamics simulations of OX2R-OXB in a pure POPC bilayer, taking 1 µs in NPT/OPLS3e ensemble with TIP3P water models and positional restriction force of 5 kcal/mol/Å 2 imposed on selected heavy atoms, confirmed nearly a whole-run stable RMSD for heavy atoms forming the OX2R-OXB interface. 27 In agreement with other in silico studies, Hong et al accepted the hypothesis that GPCRs occur in several elastic metastates on the activation potential coordinate and GPCR agonists rather shift the equilibrium towards populating more the active state than cause a conformational transition to a local energetic minimum, that is in the case of OX2R rotated outswing of TM6, upward movement of TM3, and centripetal shift of TM2.…”
Section: Introductionmentioning
confidence: 80%
“…31 Moreover, we have independently reported (R)-2, which is derived from a naphthalene-type OX2R agonist and exhibits highly potent agonist activity for both receptors (EC50 = 13.5 nM for OX1R, 0.579 nM for OX2R). 32,33 Despite the significant progress in the development of OX2R-selective and dual OX1/2R agonists, no OX1R-selective agonists have been reported so far. ).…”
Section: Introductionmentioning
confidence: 99%